Historical Analysis Exposes Catastrophic Seagrass Loss for the United Kingdom - Green, Alix E.; Unsworth, Richard K. F.; Chadwick, Michael A.; Jones, Peter J. S. (Frontiers in Plant Science, 2021)
The spatial extent of seagrass is poorly mapped, and knowledge of historical loss is limited. Here we collated empirical and qualitative data using systematic review methods to provide unique analysis on seagrass occurrence and loss in the UK. We document 8,493 ha of recently mapped seagrass in the United Kingdom since 1998. This equates to an estimated 0.9 Mt of carbon, which, in the current carbon market represents about £22 million. Using simple models to estimate seagrass declines triangulated against habitat suitability models we provide evidence of catastrophic seagrass loss; at least 44% of UK’s seagrass has been lost since 1936, 39% since the 1980’s. However, losses over longer time spans may be as high as 92%. Based on these estimates, historical seagrass meadows could have stored 11.5 Mt of carbon and supported approximately 400 million fish. Our results demonstrate the vast scale of losses and highlight the opportunities to restore seagrass to support carbon sequestration.